Piezoelectric lithotripsy and soft tissue injury. Safety limits in the experimental and clinical setting. Issue 10 (October 1990) - Darzi, A; Reid, I; Kay, E; Monson, J R; Tanner, W A; Keane, F B
Abstract : Controversy surrounds the capacity of extracorporeal shock wave lithotripsy to cause soft tissue injury. This study examines the influence of different dosages of shock waves on the gall bladder in both humans and an animal model. Sixty one guinea pigs were divided into groups and subjected to different numbers of shock waves (6, 000, 24, 000, and 48, 000) at different frequencies (2.5, 5.0, 10, 20 shock waves per second) and sacrificed at different intervals. Soft tissue damage after lithotripsy seemed to be related to the number of shock waves administered. In addition, repeated administration of low dose lithotripsy (at weekly intervals for six weeks) did not seem to produce a cumulative injury. Finally, in the animals sacrificed one month after receiving high dose lithotripsy, no soft tissue damage was evident, indicating satisfactory healing. Thirty patients were subjected to either high dose (36, 000 shock waves) or low dose (6, 000 shock waves) lithotripsy 24 hours before elective cholecystectomy. Both macroscopic and microscopic evidence of soft tissue injury were detected in a significantly higher percentage of patients who received a high dose in a single treatment (p less than 0.05). The group who received repeated low dose lithotripsy showed no evidence of cumulative injury. We conclude that low dose lithotripsy produces minimal soft tissue injury and is safe when repeated up to six times at weekly intervals.